Wanprestasi terhadap Isi dari Surat Kuasa - Ainul Mardhiyah Khaidir; Wulan Syaputri; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
This research was conducted with the aim of knowing the action of default on the contents of the power of attorney. This research belongs to the form of descriptive qualitative research, namely by providing an overview of the status of phenomena that occur in research subjects and discussed systematically and rationally. In essence, absolute power is not structured in the Civil Code, but absolute power is applied in legal traffic on the results of its development, which is in accordance with the law based on the principle of freedom of contract, as in Article 1338 paragraph (1) of the Civil Code, which states that every agreement is legally established and based on with the law, then they make it. This article is known to be the basis for freedom in making agreements and freedom of contract. The Panel of Judges also has considerations related to the decision case Number 704/Pdt.G/2017/PN.Mdn which states that if the Defendant breaks a promise alias default, as evidenced by the granting of a power of attorney that has been agreed upon but terminated by one party, and this cannot be revoked or canceled. Keywords: Code of Ethics, Advocate, Power of Attorney.